(Re) Think the evaluation… (Cuadernos de Extensión Universitaria de la UNLPam, 2019)
In the last decade, the field of University Extension acquired a greater density in the university system, with increasing legitimacy and advances in particular topics (curricularization, calls for projects, comprehensiveness functions, etc). This was not without certain obstacles in terms of budgetary conditions and academic accreditation, among other issues. The evaluation becomes relevant as a permanent compositional element of the extension process. From a reflective and dialogical perspective, which also implies a purposeful and mobilizing development, the experiences gathered on said evaluative praxis are shared in the perspective of critical extension. Thus, the shared questions are proposed as vectors that challenge and call for transforming action within the university environment itself.
Keywords: extension; evaluation; comprehensiveness of functions